Management of slipped capital femoral epiphysis: What hardware we can use in osteosynthesis in situ? - Alessandra Merenda; Francesco Falciglia; Cristian Aletto; Angelo Gabriele Aulisa; Renato Maria Toniolo (PAGEPress Publications, 2022)
Epiphysiolysis (or Slipped Capital Femoral Epiphysis, SCFE) is a hip disorder involving children during prepubescence age. Traditionally, it is defined as a postero-medial slippage of the femoral epiphysis on the metaphysis, but, considering that femoral epiphysis is almost "stored" in the acetabulum, it could be better defined as laterally and anterior slippage of femoral metaphysis under the epiphysis.